1963
DOI: 10.1037/h0043693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled coding cues in short-term memory.

Abstract: 3 experiments investigated the effects of the presence or absence of receding and decoding cues on short-terra memory (STM) for 3-letter items. The retention intervals were 3, 13, 39 sec. in Experiments I and II; 3, 12, 36 sec. in Experiment III. The Ss were 36 men and women in Experiment I, 24 in Experiment II, 30 in Experiment III. The results were (a) that receding cues facilitated STM with low meaningfulness but interfered with STM with high meaningfulness (p < .01), (b) decoding cues facilitated STM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…but when a wider range of M was employed (Experiment II), encoding cues tended to increase LM acquisition and decrease HM acquisition. Essentially these same results have been found in short-term memory for individual items by Lindley (1963) who found that encoding cues increased recall of LM trigrams but slightly decreased recall of three letter words.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…but when a wider range of M was employed (Experiment II), encoding cues tended to increase LM acquisition and decrease HM acquisition. Essentially these same results have been found in short-term memory for individual items by Lindley (1963) who found that encoding cues increased recall of LM trigrams but slightly decreased recall of three letter words.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, presentation of an encoding cue may decrease recall of a HM item. Evidence for this interpretation in short-term memory has been obtained by Lindley (1963 who found an inverse relationship between M and facilitation due to encoding cues. The present experiments study the effects of M and encoding cues in free learning.…”
mentioning
confidence: 88%
“…It has been found that giving S a coding cue along with a trigram facilitates short-term memory of that trigram (Lindley, 1963;Schaub & Lindley, 1964;Lindley & Nedler, 1965). Thus, giving S the word "view" helped S to remember VUJ.…”
Section: Discussionmentioning
confidence: 99%
“…Chunk as being in the material-the analyst's concern. Lindley (1963) performed an experiment in which he studied "the effects of the presence or absence of recoding and decoding cues on short-term memory (STM) for 3-letter items" (p. 580). These procedures are said to enable the participant to recode items into a larger "chunk" of information.…”
Section: The Uses Of the Metaphor Of Chunk In Memory Researchmentioning
confidence: 99%
“…In Lindley's (1963) article we can see how meaning enters and becomes an issue in memory research. Meaning is here taken as being in the stimulus material as such (to different degrees).…”
Section: The Uses Of the Metaphor Of Chunk In Memory Researchmentioning
confidence: 99%